Child Labor and Poverty Reduction in Vietnam - Dung, Nguyen Thu; Khuyen, Hoang Kim (University of Jember, 2021)
There is a relationship between child labor and poverty. The unaffordable financial state of households is the main reason to force children to become workers at an early age. One of the main points to respond to eliminating and preventing child labor is how to reduce poverty. Accordingly, many legal tools are designed and applied, such as forming regulations in finance supports and vocational training programs. This study provided practical evidence on the link between child labor and poverty in Vietnam as well as analysis on which legal measures the Vietnamese Government has done to tackle child labor based on the poverty approach. It was followed by some recommendations to eliminate child labor, especially in the context that negative impacts of COVID-19 pandemic push children to fall into poverty again and force them to continue to work in early-stage in most countries, including Vietnam. The study used a qualitative approach, including on desk review and a second-date analysis on regulations on child labor and poverty reduction policies in Vietnam. This study found that there existed a gap between policies on poverty to reduce child labor and practices. Comprehensive approaches in making policies, as well as law enforcement, are the core reasons. The gap should be overcome by providing unified action plans with an effective governmental authority system. KEYWORDS: Child Labor, Children Rights, Poverty Reduction.